57 Unified do not attempt resuscitation (udnacpr) orders – an audit of communication between different healthcare settings. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Sullivan, Imogen; Jackson, Tim
Abstract : Background: The use of unified Do Not Attempt Resuscitation ( 'uDNACPR') orders aims to facilitate effective communication of DNA-CPR decisions between primary and secondary care. The document remains valid in primary and secondary care facilities and ensures continuity of care. The Salford uDNACPR policy reinforces the importance of communication of such decisions with all healthcare professionals involved in the patients care. Aims/objectives: To review the quality of communication of uDNACPR decisions with General Practitioners (GPs), out of hours services and the North West Ambulance Service (NWAS) on discharge from hospital. Method: A retrospective audit included 26 patients who had a uDNACPR order introduced whilst an inpatient at Salford Royal Hospital. Data was collected from the electronic patient record, uDNACPR paper forms, GP practices, out of Hours services and the NWAS Electronic Referral Information Sharing System: 'ERISS'. Results: In 33% of cases, GPs had no record of uDNACPR decisions. The NWAS had no record of uDNACPR orders in 81% of cases, and Out of Hours services had records of only 1/26 orders. Conclusion: Current communication of uDNA-CPR decisions to community providers is inconsistent and there is clearly room for improvement. This may result in patients receiving futile and undesired interventions. One key factor identified for poor communication of uDNACPR orders was poor knowledge amongst healthcare professionals on communication channels for such decisions. Work is currently being done to facilitate and support communication to different providers on discharge from secondary care. This includes education sessions on electronic systems such as EPaCCS, discussions with the individuals responsible for 'electronic note templates' within the hospital electronic patient record and involvement in work aiming to introduce a 'Medical intraoperatively gateway' (MIG) allowing GP/hospital/other systems to communicate and share information.